FAKTOR-FAKTOR YANG MEMPENGARUHI PENYEMBUHAN LUKA GANGRENE PADA PENDERITA DIABETES MELLITUS DI RUANG RAWAT INAP RSUD DR. PIRNGADI MEDAN - Soep, Soep; Triwibowo, Cecep (Politeknik Kesehatan Kemetrian Kesehatan Medan, 2015)
Gangrenous wound healing is a state of gangrenous wounds experienced by patients with diabetes mellitus who said recovered and not recovered already passed the stage of the physiological process of wound healing gangrenous. Wound healing is a condition of the wound which has undergone phase of the physiological process of wound healing to say cured or not cured. Gangrenous wound healing is influenced by age, nutrition, wound care. The general objective of this study to determine the  factors that affect wound healing in diabetes mellitus gangrene in inpatient hospital DR.Pirngadi Medan in 2015. This research uses descriptive method with cross sectional study design. With accidential sampling techniques, sample size studied 20 respondents. Data collected by using observation sheets and questionnaires. The data obtained were analyzed manually through editing, coding, and tabulating presented in frequency distribution. Conclusion: gangrenous wound healing respondents said recovered as many as 17 people (85%), based on age ie 40-50 years as many as 10 people (50%) based nutrients are met as many as 14 people (70%), based on those wounds care done correctly by 20 (100%).